A95 HOW ENDOSCOPY TEACHERS MAKE POLYPECTOMY ENTRUSTMENT DECISIONS IN CLINICAL AND SIMULATION-BASED SETTINGS. (4th March 2021) - Jeyalingam, T; Walsh, C M; Tavares, W; Mylopoulos, M; Hodwitz, K; Liu, L W; Brydges, R
Abstract: Background: Entrustment, a central construct in competency-based medical education (CBME), represents the point at which clinical supervisors trust a trainee to perform a task independently. Many implementations of CBME involve assessing entrustment through observation of entrustable professional activities (EPAs). While EPAs are frequently assessed in both clinical and simulation-based settings, research has yet to clarify how faculty who teach endoscopy form judgments of entrustment across these two contexts. Aims: We aimed to explore the features that endoscopy teachers report as influencing their entrustment decisions regarding polypectomy across clinical and simulation-based assessment settings. Methods: We designed an interview-based, constructivist grounded theory-informed study involving endoscopy teachers and trainees in the University of Toronto gastroenterology residency program. Teachers completed separate EPA assessments of each trainee's performance of an endoscopic polypectomy (colonic polyps < 1cm, Paris 0-Is or 0-Ip in morphology) in both settings. Teachers were interviewed after each assessment to explore how they made their entrustment decision within and across settings. Transcribed interview data were coded iteratively using constant comparison to generate themes. Results: Based on 14 interviews with 7 endoscopy teachers, we found that they: (1) held multiple meanings of entrustment for polypectomy, both within and across participants, (2) expressed variability in how they justified their entrustment decisions, the related narrative, and numerical scoring, (3) held unique personal criteria for making decisions 'comfortably, ' including authenticity of the task, variability in terms of polyp shape, location, and morphology, as well as the ability to assess trainee response to procedural complications (e.g., post-polypectomy bleeding), and (4) perceived a relative freedom when using simulation to make entrustment decisions due to the absence of a real patient. Conclusions: We found that faculty who teach endoscopy defined polypectomy entrustment in a variety of ways, leading to variability in how they judged entrustment within and across trainees and assessment settings. The observed idiosyncrasies suggest gastroenterology competence committees cannot assume equivalence of EPA data obtained from different settings. Furthermore, educators designing faculty development for CBME will need to attend to the criteria that endoscopy teachers report they need to comfortably make entrustment decisions. Funding Agencies: Royal College of Physicians and Surgeons of Canada